Percursos de regresso ao trabalho após acidente: confronto com novos obstáculos - Cláudia Pereira; Marta Santos; Liliana Cunha (Universidade do Porto, 2018)
This paper discusses the obstacles the injured workers have to face upon their return to work after the accident. Two studies developed in Portugal support the analysis and the reflection on this issue. One of the studies is the outcome of a request from a company settled in the North of Portugal involving the workers with medical restrains to perform their usual work. The order consisted in an intervention to define an alternative work context. The other study, ordered by the Associação Nacional dos Deficientes e Sinistrados do Trabalho [National Association of Disabled Workers Injured On-the-job], aimed at depicting the workers' post-accident paths from different activity sectors. Three main categories of obstacles emerge from the findings, namely, when the workers return to the same function with no prior analysis and planning; when the content of the job is assigned without taking the workers' opinion into account; and when the return neglects the need for the collective work to be reorganized. The concept of the work accident as a turning point in the professional path is reinforced. The implications are always unique and the analysis to that singularity makes it possible to sign specific intervention proposals beyond the individual paths.